POWER-UP POWER PLANTS: ENERGIZING PHILIPPINES RENWABLE ENERGY SOURCES - Christel Jane V. Agaton; Mary Joy P. Cruz; John Vincent D. Gregorio; Marlyn R. Javier; Nicole Andria U. Monteron; Rohannah Anngel C. Ortiguerra; Xylee Nicole M. Parcio (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2022)
ABSTRACT This study focused on renewable energy sources in the Philippines, including solar, hydro, biomass, wind, and geothermal. The amount of energy renewable energy power plants generates and how much it costs, how many of these power plants are operating in the Philippines, and the long-term impacts of using entirely renewable energy were investigated through data mining. Among all renewable energy sources in the Philippines, geothermal power plants provide most electricity, while wind energy has the greatest production costs. A total of 235 renewable energy generating plants are active across the country, majority of them are in Luzon. Furthermore, renewable energy sources positively affect our economy and environment as they can potentially lower electric bills, increase employment, and reduce air pollution and health risks associated with it. However, potential negative consequences include lack of food security and agricultural areas. The researchers urge the government to develop more renewable energy power plants, conduct comprehensive grid-capability assessments, including assessment of potential optimal sites for new producing assets, and properly plan and handle the environmental effects. Keywords: Renewable Energy Sources, Power Plant, Philippines